Distribution of serum creatinine, calcium and protein levels in multiple myeloma patients - a hospital based study at Gauhati Medical College and Hospital, Guwahati, Assam - Lohit Kumar Kalita; Mansi Mondol; Pabitra Kamar Gogoi; Umesh Ch. Sarma (International Journal of Medical Research and Review, 2018)
Introduction: Multiple Myeloma (MM) is a clonal plasma cell neoplasm characterized by the proliferation of plasma cells, monoclonal protein, Osteolytic bone lesions, renal disease and immunodeficiency. It accounts for 15% of lymphatohematopoietic cancers (LHC) and 2% of all cancers in the US.Objectives: To see distribution of serum creatinine, calcium and protein level among MM cases.Methods: A hospital based cross-sectional descriptive study was conducted in the OPD of the clinical Haematology Department of Gauhati Medical College & Hospital, Guwahati, Assam during November, 2010 to October, 2013 with a study population of 100 in number of newly diagnosed MM) cases.Results: Serum creatinine - 54 (54%) patients had < 1.2 mg/dl, 26 (26%) patients had1.3-1.9 mg/dland20 (20%) patients had > 2 gm/dl.Serum calcium -> 11 mg/dlin 36 (36%);< 8 mg/dl in(8%) ;8 -11 mg/dl in 56 (56%) patients. Serum total protein – higher level in 52 (52%) patients. Serum albumin -< 3.5 gm/dlin 26 (26%) patients, > 3.5 gm/dlin4 (4%) patients , Normal value in70 (70%) patients. Serum globulin - < 3.5 gm/dl in 28 (28%) patients,> 3.5 gm/dl in72 (72%) patients.Conclusion: The most frequently detected SC was < 1.2 mg/ dl (84% patients),serum calcium 8-11 mg/dl (56% patients); serum total protein, albumin and globulin level were> 6.3-8.2gm/dl (52%), > 3-5 gm/dl (70%) and > 3.5 gm/dl (72 % patients) respectively.